Essential food and nutrition knowledge and skills for primary school children: Australian parents' opinions. Issue 4 (22nd November 2021) - Aydin, Gozde; Margerison, Claire; Worsley, Anthony; Booth, Alison
Abstract : Purpose: This paper examines the views of Australian primary school parents regarding the food and nutrition education (FNE) curriculum. Associations with personal values (Universalism and Hedonism) and demographic measures were also explored. Design/methodology/approach: An online survey was conducted among 787 parents in March 2021. Parents rated the importance of 17 FNE topics. They were also asked about their support for six curriculum improvements and to state their own improvement suggestions. Findings: Parents viewed the "Effect of food on health" and "Food hygiene" as the most important topics. Three FNE components were derived: (1) food safety and preparation, (2) health and nutrition information, (3) food origins and environmental sustainability. The "Food safety and preparation" component score was associated with both universalism-nature and hedonism values but negatively associated with parental education. The "Health and nutrition information" component score was associated with universalism-nature value and main language spoken at home. Lastly, the "Food origins and environmental sustainability" component score was associated with universalism-nature value. The two personal values, universalism-nature and hedonism, were more strongly associated with parents' views of curriculum topics than parental demographic characteristics. Parents had several criticisms of current FNE, including school food environments not resonating with FNE taught in the classroom and that FNE might increase the risk of eating disorders. They also suggested that the FNE curriculum should support both parents and teachers by providing relevant resources and training. Originality/value: Australian parents' views of the importance of FNE topics and how to improve FNE in primary schools have been under-examined.